Implementasi Pembelajaran Outing Class dalam Menstimulasi Motivasi Belajar Siswa - Khoiriyah, Mutiatun; Etza Sabilillah; Adelina Surya Hati Pawestri; Yulia Saputri; Bima Darma Wijaya; Taufik Muhtarom (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the implementation of outing class learning in stimulating students' learning motivation, which is expected to be a reference for contextual learning innovation. This study uses a qualitative descriptive method with data collection techniques through direct observation and interviews with teachers, school administrators, and students at Jogja Green School. The data obtained were analyzed using content analysis techniques to identify the main themes related to the impact of outing class learning on students' learning motivation. The results of the study showed that the implementation of the outing class method significantly increased students' learning motivation. Learning that involves direct experience in nature as a learning medium creates higher involvement, provides freedom to choose activities that suit students' interests, and improves character development and environmental awareness. This learning not only improves students' academic knowledge, but also life skills that can be applied in everyday life. These findings indicate that a more personal and contextual learning approach can be effective in increasing students' learning motivation.